2018
DOI: 10.1007/s10311-018-0798-4
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution of beauty salons by cosmetics from the analysis of suspensed particulate matter

Abstract: Beauty salons make a considerable part of the service sector. However, although the beauty salon staffs are exposed to a vast number of ambient chemicals during the whole workday, the occupational health hazard and the indoor air quality in beauty salons are poorly known. Specifically, reports on relations between indoor particulate matter and its outdoor or indoor sources in beauty salons are rare. Here we studied the effects of external and internal sources of aerosol in beauty salons on indoor ambient parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…An overlooked source in recent studies and discussions (Kumar et al 2013 ; Li et al 2017c ; Manigrasso et al 2018 ), candle burning can be a substantial source of indoor particle emissions (Rogula-Kopiec et al 2019 ). In the modern society, candles are no longer used primarily for lighting, but for esthetic and religious purposes such as meditation, memorials, and ceremonies, usually in indoor settings.…”
Section: Introductionmentioning
confidence: 99%
“…An overlooked source in recent studies and discussions (Kumar et al 2013 ; Li et al 2017c ; Manigrasso et al 2018 ), candle burning can be a substantial source of indoor particle emissions (Rogula-Kopiec et al 2019 ). In the modern society, candles are no longer used primarily for lighting, but for esthetic and religious purposes such as meditation, memorials, and ceremonies, usually in indoor settings.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The interaction of cosmetic based volatile organic compounds such as hydrocarbons, alcohols, esters, phenols, and acid with indoor particle matter increases the concentration and strength of particulate matter in the beauty salon. 6 Besides, the types and number of services offered and the application of cosmetics in beauty salons exert much more significant effects on the concentration level of indoor particulate matter, Volatile organic compounds (VOCs), and carbon dioxide (CO 2 ). 6,7 TVOCs are indoor air pollutants mostly produced at high concentrations in the beauty salon 2,8 with a concentration level of up to 3600 mg/m 3.9 Indoor particulate matter of different aerodynamic sizes (PM 10 and PM 2.5 ) is also one of the most harmful air pollutants with many health effects.…”
Section: Introductionmentioning
confidence: 99%
“…6 Besides, the types and number of services offered and the application of cosmetics in beauty salons exert much more significant effects on the concentration level of indoor particulate matter, Volatile organic compounds (VOCs), and carbon dioxide (CO 2 ). 6,7 TVOCs are indoor air pollutants mostly produced at high concentrations in the beauty salon 2,8 with a concentration level of up to 3600 mg/m 3.9 Indoor particulate matter of different aerodynamic sizes (PM 10 and PM 2.5 ) is also one of the most harmful air pollutants with many health effects. 10,11 Particulate matter consists of liquid droplets and solid fragments smaller than 10 µm suspended in the air, whose size, chemical composition, and shape are varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, many public lactation rooms are located in corners with an inadequate design, often as small, enclosed spaces with windowless walls. This is dangerous for the heath of mothers and babies because enclosed spaces such as schools and beauty salons are known to concentrate air pollutants (de Gennaro et al 2014 ; Rogula-Kopiec et al 2018 ). A survey of 105 lactation facilities in US university campuses revealed that over 80% of the designated spaces were structurally enclosed, and only about 40% of those places had in-room control of air temperature (Henry-Moss et al 2019 ).…”
mentioning
confidence: 99%